Bilateral Vestibular Dysfunction - Lee, Sun-Uk; Kim, Hyo-Jung; Kim, Ji-Soo (Seminars in Neurology, 2020)
Bilateral vestibular dysfunction (BVD) refers to hypofunction of the vestibular nerves or labyrinths on both sides. Patients with BVD present with dizziness, oscillopsia, and unsteadiness, mostly during locomotion, which worsen in darkness or on uneven ground. Although aminoglycoside ototoxicity, Meniere's disease, infection, and genetic disorders frequently cause BVD, the etiology remains undetermined in up to 50% of the patients. The diagnosis of BVD requires both symptoms and documentation of deficient vestibulo-ocular reflex function using head-impulse, bithermal caloric, and rotatory chair tests. Since various neurologic and systemic disorders may present with BVD, clinicians should be cautious not to overlook the symptoms and signs of central nervous system and systemic involvements. Vestibular rehabilitation, application of vibrotactile and auditory feedbacks, and vestibular prosthesis can aid the patients with BVD along with the correction of the underlying causes.
Keywords: dizziness; vertigo; oscillopsia; bilateral vestibulopathy